Study of trend facilities in the shopping complexes / Khairul Nizam Arshad - Arshad, Khairul Nizam (2003)
This study indicates that this situation is fast approaching in Malaysia. In the past the sundry shop and the wet market were the order of the day but the 70's saw the emergence of shopping complexes like Campbell and Pertama. Most of these complexes are small, congested and lacked of parking space. The 80’s the other hands saw the development of bigger purpose-built shopping complexes such Sungai Wang Plaza and Yow Chuan Plaza. These shopping centres are better designed and use the anchor tenant system to draw the crowd in. in most cases the anchor tenants are supermarkets. However in the 90’s the shopping complexes are more in tune with the recreational needs of people. Most shopping complexes also provide entertainment centre as an important features of new shopping centres. One of the trends for regional shopping complexes in Klang Valley is going for bigger and bigger shopping complexes. Another noticeable trend is the incorporation of entertainment and leisure into the overall design of mega shopping complexes. Theme parks, amusement centres etc. are planned as part and parcel of these shopping complexes to become crowd puller to achieve the critical mass essential for the viability of these mega-malls.